2014
DOI: 10.3390/md12063660
|View full text |Cite
|
Sign up to set email alerts
|

Siphonaxanthin, a Green Algal Carotenoid, as a Novel Functional Compound

Abstract: Siphonaxanthin is a specific keto-carotenoid in green algae whose bio-functional properties are yet to be identified. This review focuses on siphonaxanthin as a bioactive compound and outlines the evidence associated with functionality. Siphonaxanthin has been reported to potently inhibit the viability of human leukemia HL-60 cells via induction of apoptosis. In comparison with fucoxanthin, siphonaxanthin markedly reduced cell viability as early as 6 h after treatment. The cellular uptake of siphonaxanthin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…It exerted anti-angiogenic effect in vitro in HUVECs and in vivo in rat aortic ring model. The anti-angiogenic activity of Siphonaxanthin was accompanied by reduction in angiogenic factors like VEGF, FGF-2 and their receptors FGFR-1, EGR-1 and VEGFR-2 [55]. These findings suggest that Fucoxanthin and Siphonaxanthin have great potential to be used as anti-angiogenic drugs in future.…”
Section: Fucoxanthin and Siphonaxanthinmentioning
confidence: 73%
“…It exerted anti-angiogenic effect in vitro in HUVECs and in vivo in rat aortic ring model. The anti-angiogenic activity of Siphonaxanthin was accompanied by reduction in angiogenic factors like VEGF, FGF-2 and their receptors FGFR-1, EGR-1 and VEGFR-2 [55]. These findings suggest that Fucoxanthin and Siphonaxanthin have great potential to be used as anti-angiogenic drugs in future.…”
Section: Fucoxanthin and Siphonaxanthinmentioning
confidence: 73%
“…Siphonaxanthin (SPX; Fig. ) is a rare marine carotenoid abundant in green algae such as Codium fragile , Umbraulva japonica , and Caulerpa lentillifera (Sugawara, Ganesan, Li, Manabe, & Hirata, ). To date, antiangiogenesis, anti degranulation, and anti obesity effects of SPX have been reported but its effect on hepatic lipid metabolism remains unexplored (Ganesan et al, ; Li et al, ; Manabe, Hirata, & Sugawara, ).…”
Section: Introductionmentioning
confidence: 99%
“…Siphonein (SPN; Fig. ) has been identified as an ester form of SPX with a ester bond on its C‐19 hydroxyl group, and is present at the same level as SPX in some green algae (Sugawara et al, ). Here, we speculated that SPX possesses bioactivity with respect to suppressing hepatic lipogenesis and TAG accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…8 Also many of these compounds such as carotenoids and natural pigments have valuable roles as the antioxidant in human health. 9 However several chemical compounds such as terpenoids and steroids have been isolated from different species of the Cystoseira genus but limited histopathological studies about effects of algae extracts have been reported. 10,11 Although many of the algae are used as food source and alternative health care remedies insufficient studies on adverse effects of them clearly necessitate more investigations about them.…”
Section: Introductionmentioning
confidence: 99%